Application Of Remote Sensing And Hydrological Model For Runoff Estimation And Prediction At Upper Langat Watershed - Wong, Tai Hong (2004)

(untitled)
Rapid land development in recent years have degraded the environment and created a need for watershed modeling to quantify the impacts. During land development activities, natural flow paths in the watershed is normally being replaced or supplemented by paved gutters, storm sewers, or other form of artificial drainage. During rainfall, water remains above the land surface generating large amount of runoff within a short time. This study was carried out to evaluate the effectiveness of using HEC-HMS hydrologic model, developed in the United States for predicting surface runoff from tropical watershed. The current and future impacts of land development on runoff rate were studied. The Upper Langat River Basin with a total area of 385km2 was chosen for this study. The watershed is located in Selangor. For this study, various datasets including topographical, hydrometeorological, river cross-section and land use data were used. The land use map was derived from Landsat TM images. In order to extract land use information from remotely sensed data, two classification techniques were examined, namely pixel-based and object oriented classification. The result shows that the object oriented classification provides better accuracy (91.429%) as compared to pixel-based classification which has an overall accuracy of 81.667%. The results from model application and statistical analysis show that HEC-HMS estimated an average gap of 27% at moderate flow. During heavy rainfall, the designed model seriously overestimated the runoff with an average gap of 70%. As a conclusion, the HEC-HMS provides a conservative estimate of runoff output. It was also observed that the impact of land development on peak flow is directly proportional. Land development of 24.40km2 in year 1994 caused a peak flow of 74.62m3/s while in 1999, 50.23km2 of land development caused the peak flow of 84.04m3/s. In the proposed MSC land use plan for the year 2020, total area of 148.14km2 will be developed. This development is predicted to cause 128.15m3/s of peak flow. Therefore, it is important for urban planner to take into consideration the effect of the urbanization on the rate of runoff before developing a desired area. A well designed drainage system must be put in place during land development in order to prevent the flooding.